Vrednote slovenskih teniških igralcev - Filipič-Jeras, Ksenija (Šport (Ljubljana), 2020)
With a survey conducted in 2016, we wanted to find out what are the most important values of Slovenian tennis players. We were also interested in whether there were significant differences in their conception of gender. The sample consisted of 75 competitors of both sexes, aged 12 to 44 years. Respondents assessed the importance of 68 statements that provided reasons for engaging in sports activities. The significance of the reasons was assessed by the respondents using a five-point Likert scale. Based on the results obtained, we found that the respondents rated the value of "I like to win" the most based on competitiveness. It is followed by the values "I would like to achieve sports success with sports" and "I would like to progress to a higher level of sports with sports", which are with the first value and consequently with the competition in close content connection. The values that emphasize the importance of the influence of parents and their surroundings on playing tennis were the lowest. The association between men rankings and women rankings was high and statistically significant at one percent risk (p <0.01). In general, evaluating men was no different than evaluating women.
Keywords: gender; spol; sport; šport; tenis; teniški igralci; tennis; tennis players; values; vrednote